Public Relations: Roles, Entry Requirements and Professionalism - Cahaya Putra, Kadek Dwi (Jurnal Ilmu Komunikasi, 2009)
Abstract: This paper attempts to describe that there is a chance for non-Public Relations graduates to work as or at the Public Relations industry. Studies have shown that Public Relations practitioners are mostly from generalist background (not Public Relations) and even come into the job by chance. A Public Relations is a very sociable person, possess a mix of functional, managerial and negotiating abilities as well as analytical and well-developed communication and understand people and human psychology. With working roles of Expert Prescriber, Communication Facilitator, Problem Solving Facilitator and Communication Technician, a Public Relations needs to be well prepared by learning foreign language, joining personality improvement course, developing networking and understanding computer and communication technology. Areas of where a Public relations works are in-house (organization/company), consultancy and freelance practitioner having various titles showing their main function in the organization such as public affairs, event manager, community relations manager, marketing communication executive, employee relations manager, corporate communications manager, media coordinator. As there is an increased challenge of Public Relationsâs professionalism, a true practitioner is best prepared by educational institutions with lecturers having sound education and practice combined with extensive link-and -match research and industrial-practical placement for the graduates.